ON THE NORMALIZED RELATIVE ROUGHNESS FOR SOIL-FIBER REINFORCED POLYMER INTERFACE SHEAR BEHAVIOUR - Hussein Abed Shaia; Hossam Abuel Naga (Lowland Technology International, 2014)
Several studies in the literature have investigated the shear behaviour of soil-steel interface. Furthermore, a normalized relative roughness parameter, Rn, has been used successfully to describe the shear behaviour of the sandsteel interface. On the other hand, few studies are available in the literature regarding the interface shear behaviour of fiber reinforced polymer (FRP). The aim of this study is to investigate the shear behaviour of soil-FRP interface and examine the validity of Rn for the FRP case. Experimental program using a modified direct shear test apparatus was conducted for this purpose. The testing materials in this study include two different types of FRP, and five different-size glass beads in terms of the mean particle size, D50. The experimental results show that the interface shear behaviour of FRP is different than steel. The observed difference could be explained in terms of the expected contribution of the interface ploughing resistance in the FRP case compared to the steel where its interface shear behaviour is mainly controlled by the interface sliding resistance.